Concurrent Covalent and Supramolecular Polymerization. Issue 35 (21st July 2016) - Hou, Xisen; Ke, Chenfeng; Zhou, Yu; Xie, Zhuang; Alngadh, Ahmed; Keane, Denis T.; Nassar, Majed S.; Botros, Youssry Y.; Mirkin, Chad A.; Stoddart, J. Fraser
Abstract: Covalent and supramolecular polymerizations, both of which offer their own unique advantages, have emerged as popular strategies for making artificial materials. Herein, we describe a concurrent covalent and supramolecular polymerization strategy—namely, one which utilizes 1) a bis‐azide‐functionalized diazaperopyrenium dication that undergoes polymeriation covalently with a bis‐alkyne‐functionalized biphenyl derivative in one dimension as a result of a rapid and efficient β‐cyclodextrin(CD)‐accelerated, cucurbit[6]uril(CB)‐templated azide–alkyne cycloaddition, while 2) the aromatic core of the dication is able to dimerize in a criss‐cross fashion by dint of π–π interactions, enabling simultaneous supramolecular assembly, resulting in an extended polymer network in an orthogonal dimension. Abstract : Pushing out the polymers : A concurrent covalent and supramolecular polymerization strategy has been developed. It utilizes a rapid and efficient β‐cyclodextrin‐accelerated, cucurbit[6]uril‐templated azide–alkyne polymerization concurrently with the supramolecular assembly of diazaperopyrenium dications, which are located periodically along the polymer backbone, by dint of π–π dimerization.